Penerapan Model Pembelajaran Giving Question and Getting Answer untuk Meningkatkan Hasil Belajar IPAS Siswa SD - Sholahudin Al Ayubi; Subhanadri Subhanadri; Randi Eka Putra (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to improve the learning process and outcomes in Natural and Social Sciences (IPAS) for fourth-grade students at SDN 48/II Padang Palangeh through the implementation of the Giving Question and Getting Answer learning model. The research employed a Classroom Action Research (CAR) approach consisting of two cycles, each comprising planning, action, observation, and reflection stages. Data collection instruments included observation sheets and learning outcome tests. It can be concluded that the Giving Question and Getting Answer model is effective in enhancing students’ active participation and learning outcomes in IPAS. Observation sheets were used to monitor both student and teacher activities, while evaluation tests served as indicators of academic achievement. The analysis showed that this model significantly contributed to the improvement of both the learning process and student performance. By the second cycle, most students actively participated in classroom activities and successfully exceeded the Minimum Mastery Criteria (KKM). The results indicated a significant increase in student engagement during the learning process and a notable improvement in academic achievement from Cycle I to Cycle II. Based on these findings, it can be concluded that the Giving Question and Getting Answer approach is an effective strategy for strengthening learning outcomes and encouraging active student involvement in IPAS instruction. Additionally, the model has the potential to foster a more collaborative, communicative, and student-centered learning environment.